Redefining Russian Literary Diaspora, 1920-2020 - Rubins, Maria (FRINGE, 2021)
Over the century that has passed since the start of the massive post-revolutionary exodus, Russian literature has thrived in multiple locations around the globe. What happens to cultural vocabularies, politics of identity, literary canon and language when writers transcend the metropolitan and national boundaries and begin to negotiate new experience gained in the process of migration? Redefining Russian Literary Diaspora, 1920-2020 sets a new agenda for the study of Russian diaspora writing, countering its conventional reception as a subsidiary branch of national literature and reorienting the field from an excessive emphasis on the homeland and origins to an analysis of transnational circulations that shape extraterritorial cultural practices. Integrating a variety of conceptual perspectives, ranging from diaspora and postcolonial studies to the theories of translation and self-translation, World Literature and evolutionary literary criticism, the contributors argue for a distinct nature of diasporic literary expression predicated on hybridity, ambivalence and a sense of multiple belonging. As the complementary case studies demonstrate, diaspora narratives consistently recode historical memory, contest the mainstream discourses of Russianness, rewrite received cultural tropes and explore topics that have remained marginal or taboo in the homeland. These diverse discussions are framed by a focused examination of diaspora as a methodological perspective and its relevance for the modern human condition.